2016
DOI: 10.1177/0301006616672579
|View full text |Cite
|
Sign up to set email alerts
|

Light Video Game Play is Associated with Enhanced Visual Processing of Rapid Serial Visual Presentation Targets

Abstract: 3 AbstractThere is mixed evidence that video game players (VGPs) may demonstrate better performance in perceptual and attentional tasks than non-video game players (NVGPs). The rapid serial visual presentation (RSVP) task is one such case, where observers respond to two successive targets embedded within a stream of serially presented items. We tested light video game players (LVGPs) and NVGPs on this task. LVGPs were better at correct identification of second targets whether or not they were also attempting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…However, it is well-known that individuals can increase their perceptual abilities through training in ontogenetic time, as is seen, for example, in video-game players [6467]. We expect, therefore, the emergence of poised perception on much more rapid timescales.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is well-known that individuals can increase their perceptual abilities through training in ontogenetic time, as is seen, for example, in video-game players [6467]. We expect, therefore, the emergence of poised perception on much more rapid timescales.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the widely reported positive and beneficial effects of both SNS and video games at many levels (e.g., cognitive functioning, well-being, etc.) (e.g., Chopik, 2016 ; Heo, Chun, Lee, Lee, & Kim, 2015 ; Howard, Wilding, & Guest, 2016 ; Stroud & Whitbourne, 2015 ), there is also mounting evidence from several nationwide representative empirical studies demonstrating that SNS and video games can contribute to psychosocial impairments and behavioral dysfunction in a minority of users, including young adolescents who may use these technologies excessively and unhealthily given their current developmental stage ( Andreassen, 2015 ; Bányai et al., 2017 ; Cock et al., 2014 ; Morioka et al., 2016 ; Pápay et al., 2013 ). More recently, Sioni, Burleson, and Bekerian ( 2017 ) conducted an empirical study in a sample of 595 MMORPG players from the United States and found that addictive video game play was positively associated with symptoms of social phobia even after controlling for the shared influence of weekly gaming hours, further illustrating that socially phobic individuals prefer online forms of social interactions ( Lee & Stapinski, 2012 ) as they provide users with the unique opportunity to satisfy their social connection needs, while simultaneously allowing them to leave social situations in which they feel uncomfortable (e.g., by logging out of the game).…”
Section: Introductionmentioning
confidence: 99%
“…While Internet use is generally beneficial for peoples' life [5,6], uncontrolled Internet use and IA are highly problematic, which might damage individuals' well-being and lead to a series of adverse developmental outcomes [7,8]. A meta-analysis covering 70 studies found that the overall prevalence of IA among Chinese college students was 11.3% [9].…”
Section: Introductionmentioning
confidence: 99%